Child's Income Obligation after Divorce According to Shafi'i Sect - Lubis, Sakban (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of marriage is to get offspring;the parents are burdened to finance the life of their children. Phenomenon that occurs in some societies,this precious purpose is ignored when the marriage bond is disrupted or even severed, children are no longer properly care the education and life sustenance was ignored, as if this is not a responsibility or obligatory,from this phenomenon the writer wanted to know more the view of fiqh Syafi’iyyah towards child sustenance after divorce.This is a qualitative research with the data analysis the researcher using analysis of content,the research results show that child sustenance who have no property or sufficient after divorce, in the view of fiqh al-Syafi’iyyah the sustenance still charged to the parents. But in the implementation the father and grandfather come first if they are not capable so the child sustenance which covers all life necessities is burden into mother.